2019
DOI: 10.1097/bpo.0000000000001274
|View full text |Cite
|
Sign up to set email alerts
|

A Pediatric Medial Epicondyle Fracture Cadaveric Study Comparing Standard AP Radiographic View With the Distal Humerus Axial View

Abstract: Background: Controversy exists with regard to the amount of fracture displacement that warrants surgical fixation of medial epicondyle fractures. Inaccurate determination of degree of displacement on plain radiographs may account for the disputed management. Recently, a novel distal humerus axial radiograph technique has been developed to improve the accuracy of radiographs. The purposes of the study are 2-fold; to identify the anatomic orientation of the medial elbow epicondyle physis in children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 13 publications
0
12
1
Order By: Relevance
“…The lower reliability noted here relative to 2 previous cadaveric studies 23,32 likely represents the difference between the less than perfect real-world imaging with overlying soft-tissue swelling and a controlled cadaveric study. Once a measurement is deemed reliable, it should also reflect the true degree of separation between the 2 measurement points.…”
Section: Discussioncontrasting
confidence: 70%
“…The lower reliability noted here relative to 2 previous cadaveric studies 23,32 likely represents the difference between the less than perfect real-world imaging with overlying soft-tissue swelling and a controlled cadaveric study. Once a measurement is deemed reliable, it should also reflect the true degree of separation between the 2 measurement points.…”
Section: Discussioncontrasting
confidence: 70%
“…23 Several studies demonstrated that standard radiographic views of the elbow were unable to accurately portray the true displacement. 8,42 In particular, because the anterior displacement is significantly underestimated, 15 an internal oblique radiograph, 23 an axial view of the distal humerus, 51 and 3-dimensional computed tomography 15 are recommended to measure the true displacement of the fragment. Consequently, application of the Watson-Jones classification to the MHE fracture caused by arm wrestling, which determines the degree of displacement of the MHE fragment in the anteroposterior view, is not appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…7 The epiphysis of the MHE is a posterior structure on the distal humerus and faces backward and downward, with a reported median coronal plane angle of the physis of 36 and a median axillar plane angle of 45 . 8 Numerous muscles, including the flexor carpi radialis, flexor carpi ulnaris (FCU), palmaris longus, flexor digitorum superficialis, and part of the pronator teres, originate from the MHE, forming the flexor-pronator muscle complex (Figure 1). The pronator teres originates from not only the common tendon of the flexor-pronator muscle complex but also from the medial supracondylar ridge just proximal to the MHE, medial intermuscular septum of the arm, antebrachial fascia, and ulna.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Soft tissues were dissected and a medial epicondyle fracture was created by a pediatric orthopaedic surgeon under direct visualization using an osteotome, taking care to simulate the relatively posterior and oblique orientation typical of a medial epicondyle fracture. 23 Each fracture fragment was displaced anteriorly and inferiorly to varying degrees and secured in place with 2 stout radiolucent sutures to maintain roughly constant position throughout the imaging process. More secure Kirschner-wire (k-wire) fixation would have been ideal but produced too much imaging artifact.…”
Section: Methodsmentioning
confidence: 99%